ANALISIS KEMAMPUAN PENALARAN DEDUKTIF MATEMATIS PADA CALON GURU MATEMATIKA - Nurul Hidayah; Teguh Wibowo; Riawan Yudi Purwoko (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
Reasoning is needed in everyday life. One of the subjects that uses reasoning is mathematics. Mathematics trains a person's reasoning abilities. Mathematical deductive reasoning ability is a characteristic of mathematics itself. However, today educators tend to teach mathematics in other ways that make it difficult for students to interpret real mathematics. It is as if mathematics stands alone. Meanwhile, mathematics is born from everyday human life. In the end, many people don't like math. Therefore, this study aims to describe the mathematical deductive reasoning abilities possessed by prospective mathematics teachers. The material used is geometry. The subjects in this study were students of mathematics education in the academic year 20117/2018. Data collection techniques used observation, mathematical deductive reasoning ability test results, interview results, and field notes. The analysis technique used is in the form of data reduction, data presentation, and documentation study. Based on the results of research and discussion, prospective teachers' mathematical deductive reasoning abilities on geometry material are classified as high-level mathematical thinking skills and have been able to achieve all indicators of mathematical deductive reasoning abilities. It was also found that students were able to visualize images according to the information obtained.